ANALISIS PENGARUH INTENSITAS MODAL, LIKUIDITAS, DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI - Wibisono, Merry (Universitas Nusantara PGRI Kediri, 2023)
This study aims to test whether the intensity of capital positively affects accounting conservatism, liquidity and leverage have a positive effect on accounting conservatism. Accounting conservatism is the dependent variable in this study measured by non-operational accruals. The independent variables in this research are capital intensity, liquidity and leverage. The sample in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2012-2014. Samples were collected by using purposive sampling method and resulted in 74 companies to be sampled. Data analysis was done by classical assumption test and hypothesis test was done by multiple linear regression method using SPSS. This study concludes that capital intensity negatively affects accounting conservatism. However, leverage and liquidity have no positive impact on accounting conservatism.